Pengaruh Ekstrak Tembakau Terhadap Serangan Rayap Kayu Kering Cryptotermes Cynocephalus Light Pada Bambu Apus (Gigantochloa Apus Kurz) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Bamboo is one pf community forest products and people use it for many purposes. Due to insect attack such as termite, the time of bamboo product is short. To avoid chemical pollution in bamboo preservation process, tobacco extract was used.